Las medidas cautelares y su efecto en la violación al derecho constitucional a la salud - Karen Beatriz, Zambrano Montes (2020)
Precautionary measures from their very early creation in Roman Law until today pursue the protection of Human rights, not only in Ecuadorian Constitution, but also in International Human Rights Treaties. There is a special attention when law suffers any violation. In Ecuador, with the advent of the 2008 Constitution, jurisdictional guarantees were incorporated among them Precautionary Measures. It is a guarantee absent in the previous constitutions. It has the urgent attention; its process is fast, simple and effective. After having mentioned some antecedents about the following research "Precautionary measures and their effect on the violation of the constitutional right to health", its aim is to describe the problem through doctrinal research. The effects of precautionary measures on the violation of the Constitutional Right over health determines the mechanisms that must be applied for its compensation. To achieve this general objective, a doctrinal, documentary and bibliographic study was carried out. It provides some precautionary measure services in order to either to prevent or cease the violation of the constitutional right. Mainly, to prevent the violation of the health. If the violation of the right is proven, the judge will order its compensation.